Diagnóstico da zona de uso aquaviário e portuário de Itajaí – ZUAP (SC): bases para planejamento espacial marinho (PEM) local - Gern, Fabiana Regina (2017)
In recent years, the installation of new enterprises in the Itajaí-Açú River outfall underwent a strong pressure due to the insertion of new shipyards and marinas, as well as port expansion on both sides of the estuary. Thus the use of the waterway and port area of Itajaí becomes more intense, therefore, this situation leads to problems and conflicts, which arise due to the inefficiency in applying public planning policies and territorial planning. Therefore, this study aims to diagnose the Port and Waterway Area of Itajaí (PWAI), in order to support integrated management. Marine Spatial Planning (MSP) emerges as an innovative tool to support management, which aims to order and zone the environment, besides seeking to understand the problems and conflicts, providing opportunities for future changes to happen in a jointly manner. The methodology is based on UNESCO's guide, which presents ten steps and constitutes an adaptive and continuous process. The adapted methodology used in this study brings a low cost approach to territorial analysis and provides the integration of intersectoral visions. PWAI is considered a shelter area for navigation which enables the development of correlated and conflicting activities. The cities surrounding the PWAI have their economic development directly related to the port sector, fishing, shipbuilding and repair industry, as well as tourism and leisure. The challenge for the successful policy in MSP within the estuary of the Itajaí-Açú river lies in the assembly of all pieces of the puzzle, bringing the reconciliation between scientific research and practical solutions. Because of the holistic approach, this diagnosis can be considered as the first step to the development of a multiple use plan in the low estuary of Itajaí-Açú river.